Cytostatic conditioning in experimental allogeneic bone marrow transplantation: Busulfan causes less early gastrointestinal toxicity but Treosulfan results in improved immune reconstitution. (April 2014) - Bouazzaoui, Abdellatif; Dickhöfer, Sabine; Kreuz, Marina; Huber, Elisabeth; Holler, Ernst; Wolff, Daniel
Abstract Background: Acute graft versus host disease (aGVHD) after allogeneic bone marrow transplantation (allo-BMT) is associated with significant morbidity and mortality. We evaluated the impact of the conditioning regimen on aGVHD comparing Treosulfan (Treo) and Busulfan (Bu) with total body irradiation (TBI). Methods: Using a haploidentical murine model, B6D2F1 mice conditioned with Bu (100 mg/kg)/Fludarabine (Flu, 500 mg/kg) or Treo (6000 mg/kg)/Flu (500 mg/kg) or TBI with 14 Gy received bone marrow cells and splenocytes (20 × 106) from either syngeneic (B6D2F1) or allogeneic (C57BL/6N) donors in order to analyze aGVHD outcome. Results: Conditioning with Bu/Flu or Treo/Flu resulted in significantly reduced aGVHD severity and improved survival (p < 0.05) after allo-BMT compared to TBI. On day 5 after allo-BMT, the organ damages of Bu/Flu conditioned animals were significantly reduced in association with diminished expression of tumor necrosis factor in serum compared to Treo/Flu. Interestingly, the early toxicity of Treo/Flu did not result in significantly higher aGVHD severity; furthermore, a significantly improved immune reconstitution of B220-positive B cells was observed at day 42 after Treo/Flu conditioning compared to Bu/Flu. Conclusion: Conditioning with Treo/Flu or Bu/Flu results in decreased aGVHD severity compared to TBI. Moreover, Treo/Flu was associated with improved immune reconstitution despite the early toxicity.